Blood pressure excursions in acute ischemic stroke patients treated with intravenous thrombolysis. Issue 2 (February 2021) - Tsivgoulis, Georgios; Katsanos, Aristeidis H.; Mandava, Pitchaiah; Köhrmann, Martin; Soinne, Lauri; Barreto, Andrew D.; Sharma, Vijay K.; Mikulik, Robert; Muir, Keith W.; Rothlisberger, Travis; Grotta, James C.; Levi, Christopher R.; et al.
Abstract : Objective: To investigate the association of blood pressure BP excursions, defined as greater than 185 SBP or greater than 105 DBP, with the probability of intracranial hemorrhage (ICH) and worse functional outcomes in patients with acute ischemic stroke (AIS) treated with tissue plasminogen activator (tPA). Methods: We performed a post hoc analysis of the CLOTBUST-ER trial. Serial BP measurements were conducted using automated cuff recording according to the recommended BP protocol guidelines for tPA administration. The outcomes were prespecified efficacy and safety endpoints of CLOTBUST-ER. Results: The mean number of serial BP recordings per patient was 37. Of the 674 patients, 227 (34%) had at least one BP excursion (>185/105 mmHg) during the first 24 h following tPA-bolus. The majority of BP excursions (46%) occurred within the first 75 min from tPA-bolus. Patients with at least one BP excursion in the first 24 h following tPA bolus had significantly lower rates of independent functional outcome at 90 days (31 vs. 40.1%, P  = 0.028). The total number of BP excursions was associated with decreased odds of 24-h clinical recovery (OR = 0.88, 95% CI:0.80–0.96), 24-h neurological improvement (OR = 0.87, 95% CI: 0.81–0.94), 7-day functional improvement (common OR = 0.92, 95% CI: 0.87–0.97), 90-day functional improvement (common OR = 0.94, 95% CI: 0.88–0.98) and 90-day independent functional outcome (OR = 0.90, 95% CI: 0.82–0.98) in analyses adjusted for potential confounders. DBP excursions were independently associated with increased odds of any intracranial hemorrhage (OR = 1.26, 95% CI: 1.04–1.53). Conclusion: BP excursions above guideline thresholds during the first 24 h following tPA administration for AIS are common and are independently associated with adverse clinical outcomes. Abstract : Supplemental Digital Content is available in the text